Risk of sarcopenia in hospitalized patients and related clinical factors: a multicenter study from Turkey - (:unkn) unknown (SPRINGER, 2021)
Key summary points Aim To evaluate sarcopenia risk in hospitalized older patients. Findings The percentage of patients at risk of sarcopenia defined by the SARC-F was 48.8%. Sarcopenia risk was associated with unfavorable health care outcomes including dependency, malnutrition, and dysphagia. Message Sarcopenia risk is related with unfavorable outcomes in hospitalized patients and it is important to recognize sarcopenia at an early stage and to prevent its progression, before dependency develops. Purpose To investigate the risk of sarcopenia in hospitalized older patients and to assess the associations between sarcopenia risk and health care outcomes including dependency, malnutrition, and dysphagia. Methods This multicenter cross-sectional study was a part of the annual National Prevalence Measurement of Quality of Care (LPZ) in Turkey. Hospitalized patients age 65 and older were included in the study. The SARC-F was used to assess risk of sarcopenia. Dependency was appraised according to the Care Dependency Scale (CDS). Nutritional status was established with respect to the Malnutrition Universal Screening Tool (MUST). Dysphagia was screened by two structured questions. Results A total of 492 patients were included in the analysis. Two hundred and forty patients (48.8%) were at risk of sarcopenia. Sarcopenia risk was more prevalent among women (p = 0.007) and patients with risk of sarcopenia were older (p < 0.001). Hospital stay was longer and malnutrition and dysphagia were more prevalent in patients with sarcopenia risk than without (all p < 0.001). All nutritional interventions were applied mostly to patients with sarcopenia risk than without. In multivariate analysis, advanced age (OR: 1.068, CI 1.032-1.104, p < 0.001), female gender (OR: 2.414, CI 1.510-3.857, p < 0.001), and dependency (OR: 5.022, CI 2.922-8.632, p < 0.001) were independently associated with sarcopenia risk. Conclusions Sarcopenia risk is related with unfavorable outcomes in hospitalized patients. Primarily older female patients are at risk for sarcopenia. It is important to recognize sarcopenia at an early stage and to prevent its progression, before dependency develops. The SARC-F may be a useful tool for screening sarcopenia risk in hospitalized patients.
Keywords: Sarcopenia risk; Hospitalization; Dependency; Malnutrition; SARC-F